Analisis Efektivitas Kegiatan Ekstrakurikuler Di SDN Jaddih 5 Terhadap Peningkatan Prestasi Non Akademik - Surfilda Dwi Atika; Syailil Aliyah; Ninik Zahrotur Rohmaniyah; Andika Adinanda Siswoyo (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research focuses on the implementation of student management that has been applied through extracurricular activities. The research was conducted using several research instruments, such as observation, interviews, distribution of questionnaires and documentation. The purpose of this research is to determine the effectiveness of extracurricular activities in improving non-academic achievements, especially since many students are currently less interested in participating in extracurricular activities. The subjects of the research included the principal, extracurricular activity supervisors, and students from grades V, V, and VI, with 15 students selected from each grade. The research was conducted at SDN Jaddih over a period of approximately 1 month. From the research, it was found that there is an effectiveness of extracurricular activities at SDN Jaddih 5 in improving non-academic achievements. SDN Jaddih 5 successfully became the overall champion in the scouting competition. In addition, students benefit from the existence of these extracurricular activities.